2021
DOI: 10.3390/ijerph182010899
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Home-Based Exercise Intervention (E-Fit) on Bone Density, Muscle Function, and Quality of Life in Girls with Adolescent Idiopathic Scoliosis (AIS): A Pilot Randomized Controlled Trial

Abstract: Background: Adolescent idiopathic scoliosis (AIS) patients have lower physical activity levels than normal adolescents, and there is an association with poorer bone and muscle health. This study evaluated the effects of a home-based exercise intervention (E-Fit) on bone mineral density (BMD), muscle function, and quality of life (QoL) in AIS-affected girls. Methods: A total of 40 AIS females aged 11 to 14 years were randomly assigned to the E-Fit or control group. The E-Fit group performed modified 7-min high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…After removing 419 duplicated and 1019 unrelated studies, we finally included 56. There were 30 studies [6, on genetic risk factors related to low BMD in children with IS, eight studies on endocrine risk factors [57][58][59][60][61][62][63][64], and 18 studies [5,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] on lifestyle-related risk factors. A total of 10,768 participants with IS were included in the 56 included studies, consisting of 295 male patients with IS in 14 studies [30,31,33,38,40,43,44,48,51,56,[63][64][65][66].…”
Section: Resultsmentioning
confidence: 99%
“…After removing 419 duplicated and 1019 unrelated studies, we finally included 56. There were 30 studies [6, on genetic risk factors related to low BMD in children with IS, eight studies on endocrine risk factors [57][58][59][60][61][62][63][64], and 18 studies [5,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] on lifestyle-related risk factors. A total of 10,768 participants with IS were included in the 56 included studies, consisting of 295 male patients with IS in 14 studies [30,31,33,38,40,43,44,48,51,56,[63][64][65][66].…”
Section: Resultsmentioning
confidence: 99%
“…Another important consideration is that methods to prevent BMD loss should be proposed. Exercise is believed to increase BMD and prevent BMD loss 21 . A network meta‐analysis 22 concluded that combined exercise, resistance exercise, aerobic exercise, and mind–body exercise significantly improve the BMD of the lumbar spine, among which mind–body exercises are considered the most effective.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is believed to increase BMD and prevent BMD loss. 21 A network metaanalysis 22 concluded that combined exercise, resistance exercise, aerobic exercise, and mind-body exercise significantly improve the BMD of the lumbar spine, among which mindbody exercises are considered the most effective. Mind-body exercise is an emerging concept that involves the mind, body, psychology, and behavior.…”
Section: Prevention For Bone Mineral Density Lossmentioning
confidence: 99%
“…Some specific exercise programs for scoliosis, including E-Fit, xinmiao treatment system, and Schroth scoliosis-specific exercises, have been reported to be effective in controlling curve progression and postponing or avoiding surgical treatment. [39][40][41] The exercise-regulated serum myokine levels, whose levels in patients experiencing curve progression were reduced, not only highlight the importance of exercise-based treatment for AIS but also help to explain the underlying mechanism of myokine involvement. Extending research on how myokines halt the curve progression of patients with AIS may be beneficial in prescribing more tailored exercise prescriptions as well as myokine-based drugs.…”
Section: Discussionmentioning
confidence: 99%